2023
DOI: 10.22603/ssrr.2022-0198
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review and Meta-Analysis on the Clinical Outcomes of Spine Surgeries in Patients with Concurrent Osteoporosis

Abstract: BackgroundOsteoporosis is common among elderly patients and can result in vertebral fractures requiring surgical treatment. This study assessed clinical outcomes associated with spinal surgery in patients with osteoporosis/osteopenia with an additional focus on Asian patients. MethodsA PRISMA-compliant systematic review and meta-analysis were conducted using the PubMed and ProQuest databases to identify articles published up to May 27, 2021, that included outcomes for patients with osteoporosis or osteopenia u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The quality of this bone is therefore of importance for achieving and maintaining fixation. Ogiri et al 9 performed a metaanalysis of 133,086 patients, which demonstrated that the relative risk for screw loosening was 2.59 higher in patients with osteopenia and osteoporosis than in those with healthy bone.…”
Section: Osteoporosis and Screw-related Complicationsmentioning
confidence: 99%
“…The quality of this bone is therefore of importance for achieving and maintaining fixation. Ogiri et al 9 performed a metaanalysis of 133,086 patients, which demonstrated that the relative risk for screw loosening was 2.59 higher in patients with osteopenia and osteoporosis than in those with healthy bone.…”
Section: Osteoporosis and Screw-related Complicationsmentioning
confidence: 99%
“…The quality of this bone is therefore of importance for achieving and maintaining fixation. Ogiri et al9 performed a meta-analysis of 133,086 patients, which demonstrated that the relative risk for screw loosening was 2.59 higher in patients with osteopenia and osteoporosis than in those with healthy bone.…”
Section: Why Is Bone Density Determination Important In Spinal Surgery?mentioning
confidence: 99%
“…The spinal cord was examined and found to be decompressed, and neuromonitoring was stable from baseline. Due to the patient's history of multiple compression fractures, the patient would be at an elevated risk for proximal or distal junctional kyphosis following posterior fixation [6] . Thus, since no evidence of biomechanical instability observed, we did not pursue posterior fixation.…”
Section: Case Reportmentioning
confidence: 99%